The first peoples of Oman : Palaeolithic archaeology of the Nejd Plateu - Rose, Jeffrey I., (Archaeological heritage of Oman ;, 2019)
In Dhofar, the southern Governorate of the Sultanate of Oman, the deep canyons cutting the Nejd plateau once flowed with perennial rivers, feeding wetland environments, forests, and grasslands across the now desiccated interior. The first peoples of Oman flourished along these waterways, drawn to the freshwater springs and abundant game, as well as the myriad chert outcrops with which to fashion their hunting implements and other tools. The landscapes of the Nejd Plateau are a natural museum of human prehistory, covered in carpets of chipped stone debris. The archaeological evidence presented in this work encompasses the cultural remains of over a million years of successive human occupations, from the Lower Palaeolithic to the Late Palaeolithic.